Faecal elastase 1: a novel, highly sensitive, and specific tubeless pancreatic function test. Issue 4 (October 1996) - Löser, C; Möllgaard, A; Fölsch, U R
Abstract : BACKGROUND: Indirect pancreatic function tests available today are unreliable for clinical practice in early chronic pancreatitis due to their low sensitivity in mild and moderate exocrine pancreatic insufficiency. AIM: To evaluate the sensitivity, specificity, and practicability of faecal elastase 1 determination in patients with mild, moderate, and severe exocrine pancreatic insufficiency categorised according to the secretin-caerulein test as "gold standard'. PATIENTS AND METHODS: Faecal and duodenal elastase 1 concentration (commercial enzyme linked immunosorbent assay (ELISA)), faecal chymotrypsin activity, faecal fat analysis, and the secretin-caerulein test were performed on 44 patients with mild (n = 8), moderate (n = 14), and severe (n = 22) exocrine pancreatic insufficiency and 35 patients with gastrointestinal diseases of non-pancreatic origin. Fifty healthy volunteers were studied as normal controls. Morphological examinations were carried out to definitely confirm or exclude chronic pancreatitis. RESULTS: With a cut off of 200 micrograms elastase 1/g stool the sensitivity was 63% for mild, 100% for moderate, 100% for severe, and 93% for all patients with exocrine pancreatic insufficiency, and specificity was 93%. Values for chymotrypsin were 64% (sensitivity) and 89% (specificity). Significant (p < 0.001) correlations were found for faecal and duodenal elastase with duodenal lipase, amylase, trypsin, volume, and bicarbonate output. Individual day to day variations of faecal elastase 1 concentrations were very low (mean CV = 15%) and sample storage at room temperature is possible for at least one week. CONCLUSIONS: Faecal elastase 1 determination proved to be a highly sensitive and specific tubeless pancreatic function test.